Experimental studies on freshwater zooplankton in Brazil: a scientometric analysis from 1978 to 2023 - Portinho, Jorge Laço [UNESP]; Brandão, Larissa Ferreira [UNESP]; Machado, Marco Antonio Azevedo [UNESP]; Nova, Clarice Casa; Bandeira, Maiby Glorize da Silva; Dias, Juliana Deo; Ferreira, Amanda Costa [UNESP]; Bozelli, Reinaldo Luiz (FapUNIFESP (SciELO), 2024)
Aim: This study aims to contribute to elucidating the importance of experimental research on freshwater zooplankton communities in Brazil through a scientometric analysis. Methods: Web of Science, SciELO, and Scopus databases were used to compile 249 scientific papers published between 1978 and 2023. The extracted data included the year of publication, geographical location, experiment characteristics (type, scale, duration), species or taxa studied, and research topics. Quantitative and qualitative syntheses were performed to provide a systematic understanding of experimental studies on freshwater zooplankton. Results: The analysis revealed a significant increase in the number of experimental papers over time, with a higher concentration of studies in the Southeastern region of Brazil. Laboratory experiments were conducted with greater frequency than field experiments, mainly microcosms. Predation, chemical pollutants, and eutrophication emerged as frequently addressed research topics. On the other hand, certain topics, such as metapopulation dynamics and microplastics, were relatively underrepresented in the literature. Despite the crucial role of experimental research on freshwater zooplankton in advancing ecological understanding in Brazil, there is an unequal distribution of these studies across the country, indicating the need for investment and more researchers prepared and interested in studying with experiments in certain regions. Addressing the gaps identified in this review, such as metapopulation dynamics and dispersion, along with emerging threats like invasions, microplastics, pathogens, cumulative stressors, emerging contaminants, and nanomaterials, will be essential for generating scientific knowledge to inform effective management strategies to preserve freshwater zooplankton biodiversity amidst ongoing environmental changes. Conclusions: This review underscores the importance of expanding experimental research across diverse regions and underexplored topics to enhance our ecological understanding and better manage freshwater zooplankton biodiversity in Brazil.
Estudos experimentais sobre zooplâncton de água doce no Brasil: uma análise cienciométrica de 1978 a 2023
Keywords: duration of experiments; field experiment; laboratory experiment; systematic review